Advancing the thermodynamic approach with the predictive model for the freeze-drying of meat - Oztuna Taner, Oznur (Frontiers in Sustainable Food Systems, 2025)
The establishment of innovative engineering techniques for meat products is required because of the significant energy requirements associated with freeze-drying of food products. This study is innovative application research on the freeze-drying of meat process and analyses energy efficiency by employing predictive statistical methods. Thermodynamic laws play a crucial role in the thermodynamic analysis of frozen food processes by regulating the essential operations involved in food production. The thermodynamic evaluation of the freeze-drying of meat process was carried out over a total of 40 scenarios covering 24 h (20 scenarios) and 30 h (20 scenarios). The energy efficiency in the 24 h process fluctuated between 38.7 and 43.1% over the 20 scenarios, whereas in the 30 h process, it varied from 36.9 to 41.1% throughout the 20 scenarios. The analysis revealed that the energy efficiency of the 24 h scenarios exceeded that of the 30 h scenarios, suggesting that 24 h is the optimum period for meat drying. This comparative assessment indicates that shortening the drying duration can deliver substantial energy savings without compromising process effectiveness. Future research will look at the application of this technology to enhance food quality and shelf life by applying a comparable freeze-drying technique to meat in various food industries.